Politik Hukum Keuangan Partai Politik di Indonesia: Dalam Perspektif Model Pengaturan Partai Politik - Andika Wahyudi Gani; Sirajuddin Saleh (Seminar Nasional LP2M UNM, 2021)
Abstract. One of the hearts of the functioning of democracy is political parties, to ensure the sustainability of the life of political parties, access to the funds of political parties is essential. However, on the other side, money has a significant destructive potential to democracy if it is not governed proportionally. This research tries to investigate and comprehend the financial arrangements of political parties. This form of study is normative research, focused on secondary data consisting of primary and secondary legal documents, then qualitatively examined. The financial regulation of political parties in Indonesia comprises the restriction of funding sources, quantity or amount and oversight through the accountability reporting system. However, access to public money does not include non-financial support in the form of natural, as well as the provision of advice on public funds on a timely basis following the model of granting subsidies after the general election.Keywords: Politic of Law, Finance, Political Party, Regulatory Model